2017
DOI: 10.1534/g3.117.042093
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Satellite DNA Landscape in Three CactophilicDrosophilaSequenced Genomes

Abstract: Eukaryote genomes are replete with repetitive DNAs. This class includes tandemly repeated satellite DNAs (satDNA) which are among the most abundant, fast evolving (yet poorly studied) genomic components. Here, we used high-throughput sequencing data from three cactophilic Drosophila species, D. buzzatii, D. seriema, and D. mojavensis, to access and study their whole satDNA landscape. In total, the RepeatExplorer software identified five satDNAs, three previously described (pBuM, DBC-150 and CDSTR198) and two n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 94 publications
1
25
0
Order By: Relevance
“…gambiae will contribute to higher genetic differentiation, and will eventually lead to postzygotic reproductive isolation between some populations of these important disease vectors. Extensive studies of Drosophila species show that heterochromatin, in general, and satellite DNA, in particular, can be a source of tremendous genetic variation [76][77][78][79][80]. Heterochromatin can also modulate differential gene expression and cause variable phenotypes, including differences in immune response [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…gambiae will contribute to higher genetic differentiation, and will eventually lead to postzygotic reproductive isolation between some populations of these important disease vectors. Extensive studies of Drosophila species show that heterochromatin, in general, and satellite DNA, in particular, can be a source of tremendous genetic variation [76][77][78][79][80]. Heterochromatin can also modulate differential gene expression and cause variable phenotypes, including differences in immune response [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, short arrays of satDNAs dispersed along the euchromatin have been described. There are also satDNAs present not exclusively within heterochromatin but also dispersed as single repeats or short arrays within euchromatin [ 14 , 21 , 80 , 85 , 127 , 128 , 129 , 130 , 131 ]. Similarly, shorter repeats showed the same capability to cluster both in euchromatin and in heterochromatin.…”
Section: Changing Conceptsmentioning
confidence: 99%
“…Different arrays on the same or in different chromosomes may experience independent homogenization for arrays- or chromosome-specific repeat variants [ 122 , 127 , 131 , 201 ]. Thus, the analysis of euchromatic and heterochromatic repeats from 52 arrays showed that the homogenization of satDNA repeats of the 1688 satDNA family of Drosophila occurred differentially for distinct genomic regions, from euchromatin to heterochromatin and from local arrays to chromosomes [ 127 ].…”
Section: Changing Conceptsmentioning
confidence: 99%
“…The data generated is now being used to determine satDNA sequences organization in the genome [95], explore predicted evolutionary patterns and hypothesis (e.g., [35,68,96,97]), as well as to shed light into the function of these sequences [81,98]. We are now closer than ever to fully access the sequence information hidden within repetitive-rich chromosome structures like centromeres and telomeres.…”
Section: Satdna Features and Organization In The Genome And Chromosommentioning
confidence: 99%